2020
DOI: 10.2196/16928
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Need and Acceptability of an App to Support Activities of Daily Living in People With Cognitive Impairment and Their Carers: Pilot Survey Study

Abstract: Background Modern technologies, including smartphone apps, have the potential to assist people with cognitive impairment with activities of daily living, allowing them to maintain their independence and reduce carer burden. However, such tools have seen a slow rate of uptake in this population, and data on the acceptability of assistive technologies in this population are limited. Objective This pilot study included older adults with cognitive impairmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 17 publications
2
19
0
2
Order By: Relevance
“…Similarly, concerns about the ease of use of the technology with strong recommendations from all 3 groups regarding the integration of voice commands also underline the benefits of including people with MCI or ADRD in the development of products or interventions for which they are the primary target as well as family caregivers and clinicians. Our findings echo previous studies that highlight the importance of aligning and customizing technology functions and applications to end-product users [ 12 , 18 , 19 , 28 - 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, concerns about the ease of use of the technology with strong recommendations from all 3 groups regarding the integration of voice commands also underline the benefits of including people with MCI or ADRD in the development of products or interventions for which they are the primary target as well as family caregivers and clinicians. Our findings echo previous studies that highlight the importance of aligning and customizing technology functions and applications to end-product users [ 12 , 18 , 19 , 28 - 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the stakeholder group participants share a widespread belief about the benefits of technology in general and about the Generation Connect platform, specifically with regard to the platform’s support efforts for caring for individuals with dementia in their homes. In general, this finding supports the benefit of technology acceptance for promoting technology use [ 21 - 24 ]. It is clear that in this case, familiarity breeds acceptance, with many FCGs reporting using the Generation Connect platform during their shifts.…”
Section: Discussionsupporting
confidence: 72%
“…Approximately 7% (2/28) of studies targeted caregivers who reported being isolated [ 56 ] or experiencing caregiving strain [ 38 ]. Caregivers most commonly provided care to older adults with dementia or other forms of cognitive impairment [ 37 - 39 , 41 - 44 , 46 , 47 , 50 - 56 , 58 - 60 , 62 , 64 ]. Other studies recruited caregivers who provided care to older adults with urinary incontinence [ 63 ], older veterans who were medically complex [ 45 ], and older adults with functional loss or struggling to remain independent at home [ 49 , 57 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Potential sources of bias within other quantitative studies include a lack of control groups [ 60 , 62 , 63 ] and limited consideration of potential confounders [ 41 , 56 ]. Most of the included quantitative studies recruited small convenience samples of caregivers or caregiver–care recipient dyads; for example, recruiting from single clinics [ 38 , 39 ] or from attendees of an Alzheimer’s Association chapter event [ 50 ]. Included qualitative studies were most often limited by a lack of clear alignment between philosophical underpinnings, methodology, and research questions or objectives [ 49 - 53 , 55 - 58 , 60 , 62 ].…”
Section: Resultsmentioning
confidence: 99%